Preoperative Risk Factors for Early Postoperative Bleeding after Roux-en-Y Gastric Bypass: A Systematic Review and Meta-Analysis - Alexandre Pedro e Silva (2021)
Background: Early postoperative bleeding is one of the most common complications after Roux-en-Y gastric bypass (RYGB) surgery. Its occurrence is associated with a worsening of postoperative outcomes and a higher postoperative mortality rate. This systematic review and meta-analysis aimed to find preoperative risk factors for early postoperative bleeding after RYGB surgery and quantify their impact. Methods: The investigators searched MEDLINE, Scopus, Web of Science and gray literature for experimental or observational studies, published up to December 2020. A random effects model was used to determine pooled estimates of the results. The primary occurrence was early postoperative bleeding after Roux-en-Y gastric bypass surgery in patients with and without a given preoperative factor. Results: In total, 13 studies, including 162,982 patients, were included in our systematic review. All were eligible for our meta-analysis. Our meta-analysis revealed that male gender (odds ratio (OR)=1.39, 95% confidence interval (CI) = 1.12-1.73, p=0.003), arterial hypertension (OR=1.55, 95%CI = 1.25-1.85, p<0.0001), dyslipidemia (OR=1.42, 95%CI = 1.02-1.98, p=0.04) and a previous bariatric surgery (implying revisional RYGB surgery) (OR=1.35, 95%CI = 1.08-1.68, p=0.008) were associated with early postoperative bleeding after RYGB surgery. On the other hand, age (mean difference=2.75 years, 95%CI =-0.09-5.60, p=0.06), superobesity (OR=0.99, 95%CI = 0.84-1.18, p=0.96), diabetes mellitus (OR=1.33, 95%CI = 0.74-2.39, p=0.35) and obstructive sleep apnea (OSA) (OR=1.24, 95%CI = 0.96-1.58, p=0.09) were not proven to be associated with this complication. Conclusion: In this systematic review and meta-analysis, male gender, arterial hypertension, dyslipidemia and previous bariatric surgery were associated with a higher rate of early postoperative bleeding after RYGB surgery. This association was not proven with age, superobesity, diabetes mellitus and OSA. Further investigation on preoperative risk factors for early postoperative bleeding after RYGB is required to confirm these results.